RESPIRATION AND MICROBIAL BIOMASS IN SOIL UNDER DIFFERENT SYSTEMS OF USE - KUMMER, Larissa; BARROS, Yara Jurema; SCHÄFER, Rossana Ferrari; FERREIRA, Anna Tereza dos Santos; FREITAS, Mônica Paul; PAULA, Rodrigo Aquino de; DIONÍSIO, Jair Alves (Scientia Agraria, 2008)
The respiration and microbial biomass are important biological indicators of the soil quality. Therefore, the present work had as objective to evaluate the influence of four systems of soil use on the basal respiration (BR) and substrate induced respiration (SIR) and, also, soil microbial biomass (SMB). The studied areas belong to the Sector of Agrarian Sciences of the UFPR: Cassia (grouping of Senna pendula), Forest (arboreal species), Pasture (grasses) and Agroecology (agroecologic culture of vegetables). The samples were collected in the depth of 0-10 cm, and determined by titulometric measurements the BR, SIR and the SMB (glucose addition). Were not observed diferences amoung the studies areas relatively to SIR with sugar cane and SMB. However, the BR in Agroecology, Pasture and Forest, and the SIR with maize in Cassia and Agroecology were majors. The addition of maize and sugar cane residues increased the BR, mainly in the SIR with maize, because your lowest C/N relation.